Kwestia bogatych pochówków kobiecych w antycznej Tracji - Hatłas, Jerzy (Folia Praehistorica Posnaniensia, 2018)
The article discusses the most important opinions of Bulgarian scholars on rich women burials in ancient Thracia. Analysis of subsequent sites, along with the newest archaeological discoveries (in particular, a burial from mound 47 at Smjadovo), makes possible to conclude that such burials really existed on the discussed territory, or at least on its part.